Solubility and Dissolution Enhancement of Atorvastatin Calcium using Solid Dispersion Adsorbate Technique - Samer K. Ali; Eman B. H. Al-Khedairy (College of Pharmacy University of Baghdad, 2019)
Atorvastatin (ATR) is poorly soluble anti-hyperlipidemic drug; it belongs to the class II group according to the biopharmaceutical classification system (BCS) with low bioavailability due to its low solubility. Solid dispersions adsorbate is an effective technique for enhancing the solubility and dissolution of poorly soluble drugs.           The present study aims to enhance the solubility and dissolution rate of ATR using solid dispersion adsorption technique in comparison with ordinary solid dispersion. polyethylene glycol 4000 (PEG 4000), polyethylene glycol 6000 (PEG 6000), Poloxamer188 and Poloxamer 407were used as hydrophilic carriers and Aerosil 200, Aerosil 300 and magnesium aluminium silicate (MAS) as adsorbents.            All solid dispersion adsorbate (SDA) formulas  were prepared in ratios of 1:1:1  (drug: carrier: adsorbent) and evaluated for their water solubility, percentage yield, drug content,  , dissolution, crystal structure using  X-ray powder diffraction (XRD) and Differential Scanning Calorimetry (DSC)  studies and Fourier Transform Infrared Spectroscopy (FTIR) for determination the drug-carrier- adsorbate interaction.                The prepared (SDA) showed significant improvement of drug solubility in all prepared formula. Best result was obtained with formula SDA12(ATR :Poloxamer407 : MAS 1:1:1) that showed 8.07 and 5.38  fold increase in solubility compared to  solubility of pure ATR and  solid dispersion(SD4) (Atorvastatin: Poloxamer 407 1:1) respectively due to increased wettability and reduced crystallinity of the drug which leads to improve drug solubility  and  dissolution .